Exploring rhythmic pattern in blind runners: a pilot study - Di Martino, G.; Della Valle, C.; Alario, M.; Persichini, L.; Pavese, I.; Perna, F.; Virzi, M.; Calcagno, G.; Di Cagno, A.; Iuliano, E. (Medicina dello Sport, 2024)
BACKGROUND: This is an observational pilot study comparing kinematic variables of running between blind athletes and sighted athletes. Aim was to verify significant differences in the rhythmic pattern of fast running between male sighted and blind athletes, with similar anthropometric parameters and performance skills.